2014
DOI: 10.5562/cca2436
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Liquid Extraction-Spectrophotometric Investigations of Three Ternary Complexes of Vanadium(V)

Abstract: Abstract. Complex formation and liquid-liquid extraction (LLE) were studied in systems containing vanadium(V), 5-methyl-4-(2-thiazolylazo)resorcinol (TAO), tetrazolium salt (TZS), water and chloroform. The following three TZSs were used: 3-(4,5-dimethyl-2-thiazol)-2,5-diphenyl-2H-tetrazolium bromide (MTT), 3-(2-naphtyl)-2,5-diphenyl-2H-tetrazolium chloride (Tetrazolium violet, TV), and 2-(4-iodophenyl)-3-(4-nitrophenyl)-5-phenyl-2H-tetrazolium chloride (INT). Concentration of the reagents (TAO and TZS), pH of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…, and then formed ion-pairing complexes with hydrophobic amines , o-, m-and p-toluidine derivatives (as R-NH 3 + ) detected by both spectrophotometry and ESR spectrometry. 44 Moreover, so as to support the mechanism of complex formation, from potentiometric titration data obtained in two separate studies, 45,46 including other studies based on ion-association, 47,48 it has been observed that pK a value of chelate complex formed between vanadyl ion, VO 2+ and pyrogallol at pHs near to neutral is 5.40 where it spontaneously forms a highly stable complex with a logK f ranging from 22.97 to 21.68 at pHs near to neutral, gradually decreasing with increasing temperature in range of 25-45 °C. Also, under optimal conditions, it has been ob-served that after pre-reduction and hydrolysis in absence and presence of safranin T as ion pair, vanadium is complexed with pyrogallol in form of anionic VO(OH)L 2 with a logK f of 20.9 with relative error of -3.6% at pH 6.0, and then extracted as the hydrophobic ternary complex in form of VO(OH)L 2 SF into the micellar phase with stoichiometric ratios 1:2 and 1:2:1, as determined using the molar ratio and Job's continuous variation methods.…”
Section: -mentioning
confidence: 98%
“…, and then formed ion-pairing complexes with hydrophobic amines , o-, m-and p-toluidine derivatives (as R-NH 3 + ) detected by both spectrophotometry and ESR spectrometry. 44 Moreover, so as to support the mechanism of complex formation, from potentiometric titration data obtained in two separate studies, 45,46 including other studies based on ion-association, 47,48 it has been observed that pK a value of chelate complex formed between vanadyl ion, VO 2+ and pyrogallol at pHs near to neutral is 5.40 where it spontaneously forms a highly stable complex with a logK f ranging from 22.97 to 21.68 at pHs near to neutral, gradually decreasing with increasing temperature in range of 25-45 °C. Also, under optimal conditions, it has been ob-served that after pre-reduction and hydrolysis in absence and presence of safranin T as ion pair, vanadium is complexed with pyrogallol in form of anionic VO(OH)L 2 with a logK f of 20.9 with relative error of -3.6% at pH 6.0, and then extracted as the hydrophobic ternary complex in form of VO(OH)L 2 SF into the micellar phase with stoichiometric ratios 1:2 and 1:2:1, as determined using the molar ratio and Job's continuous variation methods.…”
Section: -mentioning
confidence: 98%
“…5,6,9,10 The following ACs were investigated as components of ternary V(V)-AC-TZ complexes: 4-(2-pyridylazo)resorcinol 10-12 , 4-(2-thiazolylazo)resorcinol, 13,14 and 4-(2-thiazolylazo)orcinol (TAO). 15 The obtained results show that the V(V):AC molar ratio in these complexes differs, [11][12][13][14][15] as a rule, from the typical 1:1 ratio established in the presence of other ion-association reagents (Table S1). However, the reason for this peculiarity is unclear and quantum-chemical calculations on V-AC-TZ ternary complexes have never been conducted.…”
Section: Introductionmentioning
confidence: 96%
“…sar-Boltz method 35 ( Figure 6), extended by the equation 5, proposed in our previous paper 15 for this kind of complexes.…”
Section: V(v)mentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25][26][27][28] It has recently been used in our laboratory for LLE of V IV,V . [29][30][31][32] Here, we describe investigations on a LLE-chromogenic system for Ni II containing MTAR and the ionic liquid Aliquat 336 (A336). The selected organic solvent was isobutanol (2-methylpropan-1-ol).…”
Section: Introductionmentioning
confidence: 99%